Persistent Helicobacter pylori Specific Th17 Responses in Patients with Past H. pylori Infection Are Associated with Elevated Gastric Mucosal IL-1β - Serelli-Lee, Victoria; Ling, Khoon Lin; Ho, Cassandra; Yeong, Lai Han; Lim, Gek Keow; Ho, Bow; Wong, Soon Boon Justin (PLOS ONE, 2012)
Background Ongoing Helicobacter pylori (HP) infection triggers a chronic active gastritis. Eradicating HP reduces gastric inflammation, but does not eliminate it. We sought to characterize this persistent gastritis, and demonstrate the persistence of HP-specific Th17 responses in individuals previously infected with HP but who no longer had evidence of ongoing infection. Methodology/Principal Findings Study subjects were divided into 3 groups 55 individuals had active HP infection (group A), 41 were diagnosed with previous HP infection (group P), and 59 were naïve to HP (group N). Blood and gastric tissue were obtained with written informed consent from all subjects, and immune responses were evaluated using flow cytometry, semi-quantitative real time PCR, immunofluorescent staining, ELISA, and multiplex cytometric bead array for cytokine quantification. Elevated IL-17A responses were observed in patients from group A compared to group N. Interestingly, IL-17A responses remained persistently elevated in the blood and gastric mucosa of individuals from group P, despite the absence of ongoing HP infection. Using purified CD4+ T cells as effectors and antibodies that blocked antigen presentation by MHC Class II, we showed that these persistent IL-17A responses were mediated primarily by HP-specific Th17 cells, rather than other immune cells that have also been described to secrete IL-17A. Gastric mucosal IL-1β levels were also persistently elevated in group P, and neutralisation of IL-1β reduced the HP-specific IL-17A response of purified CD4+ T cells to autologous HP-pulsed antigen presenting cells in vitro, suggesting a functional association between IL-1β and the persistent Th17 response in group P patients. Conclusions/Significance Despite lack of ongoing HP infection, HP-specific Th17 cells persist in the blood and gastric mucosa of individuals with past HP infection. We speculate that this persistent inflammation might contribute to gastric mucosal pathology, for example, persistent increased gastric cancer risk despite eradication of HP.